Analisis Semiotika Roland Barthes dalam Respresentasi “Genosida Palestina” pada Karya Foto Motaz Azaiza - Syahkist Afi Daib; Sidiq Setyawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the signs and messages contained in Motaz Azaiza's photographs depicting the genocide in Palestine. In the era of technological development, photography has become an effective medium for conveying information and events to the public. Motaz Azaiza, as a famous photographer from Palestine, has succeeded in drawing the world's attention to the issue of genocide through his works that are rich in meaning and symbols. The method used in this study is a qualitative approach with a descriptive design. Primary data was obtained from the Instagram account @motaz_azaiza with data collection techniques through documentation and observation. This study also applies a data credibility test through triangulation, which compares observational data and documentation to ensure the accuracy of the information obtained. The results of the study show that Azaiza's photographs not only present the genocide event, but also contain a deep message about the condition of civil society in Palestine. Through semiotic analysis, this study identifies various signs that present complex social and political phenomena. This study is expected to contribute to semiotic studies in understanding how genocide visualization can influence public perception of the conflict in Palestine.